Tiempos de la historia, tiempos de la cultura - Santiago, Dulce María (Sapientia, 2022)
This paper aims to introduce Francisco Leocata’s research on cultural configuration of Argentine ideas (I), as well as his suggested period setting (II). The timespan of Leocata’s research ranges from the end of XVI century to the beginning of XXIst. The place is now Argentina and has always been part of the South Cone.